Exploring Effective Approaches: Integrating Mental Health Services into HIV Clinics in Northern Uganda - Kabunga A; Namata H; Kigongo E; Musinguzi M; Tumwesigye R; Auma AG; Nabaziwa J; Shikanga EM; Okalo P; Nalwoga V; Udho S (HIV/AIDS: Research and Palliative Care, 2024)
Amir Kabunga,1 Halimah Namata,2 Eustes Kigongo,3 Marvin Musinguzi,4 Raymond Tumwesigye,5 Anna Grace Auma,6 Jannat Nabaziwa,4 Enos Mwirotsi Shikanga,7,8 Ponsiano Okalo,1 Viola Nalwoga,1 Samson Udho9 1Department of Psychiatry, Lira University, Lira City, Uganda; 2Department of Mental Health, Makerere University, Lira City, Uganda; 3Department of Environmental Health and Disease Control, Lira University, Lira City, Uganda; 4Department of Community Health, Lira University, Lira City, Uganda; 5Department of Critical Nursing, Mbarara University of Science and Technology, Mbarara City, Uganda; 6Department of Nursing, Lira University, Lira City, Uganda; 7Department of Education Psychology, Moi University, Eldoret City, Kenya; 8Department of Psychiatry, Gulu University, Gulu City, Uganda; 9Department of Midwifery, Lira University, Lira City, UgandaCorrespondence: Amir Kabunga, Department of Psychiatry, Lira University, P.O. Box, 1035, Lira City, Uganda, Tel +256777929576, Email amirkabs2017@gmail.comBackground: Integrating mental health services into HIV clinics is recognized as a promising strategy. However, the literature reveals gaps, particularly in the unique context of Northern Uganda, where factors such as historical conflict, stigma, and limited resources pose potential barriers.Material and Methods: This qualitative study, conducted between October and November 2023, employed a phenomenological design. The study involved primary healthcare facilities across diverse urban and rural settings, focusing on healthcare providers, village health teams, and service users. A purposive sampling approach ensured diverse demographics and perspectives. In-depth interviews and focus group discussions were conducted, with healthcare providers and service users participating individually, and village health teams engaged in group discussions. Thematic analysis was employed during data analysis.Results: Findings revealed a predominance of females among healthcare providers (18 of 30) and service users (16 of 25), as well as in VHTs. Average ages were 33.4 (healthcare providers), 38.5 (service users), and 35.1 (VHTs). Most healthcare providers (15) held diplomas, while 12 service users and 4 VHTs had certificates. The majority of healthcare providers (n=20) and 4 VHTs had 6– 10 years of experience. Thematic analysis highlighted three key themes: benefits of integrated mental health services, implementation challenges, and the role of community engagement and cultural sensitivity.Conclusion: This study contributes valuable insights into the integration of mental health services into HIV clinics in Northern Uganda. The perceived benefits, challenges, and importance of cultural sensitivity and community engagement should guide future interventions, fostering a holistic approach that enhances the overall well-being of individuals living with HIV/AIDS in the region. Policymakers can use this information to advocate for resource allocation, training programs, and policy changes that support the integration of mental health services into HIV clinics in a way that addresses the identified challenges.Keywords: HIV clinic, integration, mental health disorder, Uganda